Psychometric evaluation of the student nurse stressor-14 scale for undergraduate nursing interns - Jingjing Ding; Yang Yu; Jie Kong; Qing Chen; Patricia McAleer (BMC, 2023)
Abstract Background Currently, there are few scales used to assess the stressors experienced by undergraduate nursing interns during clinical practice, and the assessment of stressors during clinical practice is not comprehensive; the scale includes some unique stressors during training that is not available in the existing instruments used to assess nursing student practice stress in China. Aim The study aimed to explore the structure of the Chinese revision of the Student Nurse Stressor-14 Scale(SNS-14-CHI)and investigate the psychometric properties it among Chinese undergraduate nursing interns. Methods The original scale was culturally adjusted and revised after expert correspondence on the entries, and 414 undergraduate nursing interns were recruited from three cities in China to administer the questionnaire. Reliability was measured by internal consistency, fold-half reliability, and stability. Content validity was evaluated using exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) to assess the validity of the SNS-14-CHI. Results The SNS-14-CHI retained 14 items, the EFA supported a 2-factor structure, and the items' factor attribution differed from the original scale. The CFA results showed a good model fit. The Cronbach coefficient of the scale was 0.934, and the coefficient values of the two factors were 0.890 and 0.898. The content validity index of the scale was 0.964.The cumulative variance contribution of the 2-factor structure was 60.445%. The split-half reliability and stability were 0.869,0.762, respectively. Conclusion The SNS-14-CHI has excellent reliability and validity among undergraduate nursing trainees. The evaluation results of the scale can provide a reference for nursing managers to develop educational programs and interventions to quantify nursing student stress.